2012
DOI: 10.1152/ajpgi.00441.2011
|View full text |Cite
|
Sign up to set email alerts
|

Direct methylation of FXR by Set7/9, a lysine methyltransferase, regulates the expression of FXR target genes

Abstract: The farnesoid X receptor (FXR) is a ligand (bile acid)-dependent nuclear receptor that regulates target genes involved in every aspect of bile acid homeostasis. Upon binding of ligand, FXR recruits an array of coactivators and associated proteins, some of which have intrinsic enzymatic activity that modify histones or even components of the transcriptional complex. In this study, we show chromatin occupancy by the Set7/9 methyltransferase at the FXR response element (FXRE) and direct methylation of FXR in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…ChIP assays demonstrated the recruitment of Set7/9 and the presence of the associated H3K4 monomethylation activation mark at the loci of two of the known FXR hepatic targets, the small heterodimer partner NR0B2 (SHP) and BSEP. This significantly enhanced the transcription of these two FXR target genes (Balasubramaniyan et al 2012). Similar data for AR (Ko et al 2011) and ER (Subramanian et al 2008) indicate that this mechanism could also possibly stabilize FXR and promote its interaction with its heterodimerization partner RXR and the FXRE (Balasubramaniyan et al 2012).…”
Section: Post-induction Histone Modificationsmentioning
confidence: 54%
See 2 more Smart Citations
“…ChIP assays demonstrated the recruitment of Set7/9 and the presence of the associated H3K4 monomethylation activation mark at the loci of two of the known FXR hepatic targets, the small heterodimer partner NR0B2 (SHP) and BSEP. This significantly enhanced the transcription of these two FXR target genes (Balasubramaniyan et al 2012). Similar data for AR (Ko et al 2011) and ER (Subramanian et al 2008) indicate that this mechanism could also possibly stabilize FXR and promote its interaction with its heterodimerization partner RXR and the FXRE (Balasubramaniyan et al 2012).…”
Section: Post-induction Histone Modificationsmentioning
confidence: 54%
“…This significantly enhanced the transcription of these two FXR target genes (Balasubramaniyan et al 2012). Similar data for AR (Ko et al 2011) and ER (Subramanian et al 2008) indicate that this mechanism could also possibly stabilize FXR and promote its interaction with its heterodimerization partner RXR and the FXRE (Balasubramaniyan et al 2012). Furthermore, recruitment of chromatin-remodelling proteins and NR-dependent gene transcription is a very dynamic process and different co-regulators and chromatin-remodelling proteins can occupy different REs of the same NR.…”
Section: Post-induction Histone Modificationsmentioning
confidence: 59%
See 1 more Smart Citation
“…Moreover, Li et al (2007) and Kemper et al (2009) reported that SIRT1 [sirtuin (silent mating type information regulation 2 homolog) 1; a highly conserved NAD 1 -dependent protein deacetylase] is a positive regulator of liver X receptor and FXR. The data from our laboratory also demonstrated that direct methylation of FXR by lysine methyltransferase Set7/9 regulates the expression of FXR target genes (Balasubramaniyan et al, 2012). Posttranslational modifications at specific lysine residues of NRs dx.doi.org/10.1124/mol.113.084772.…”
Section: Introductionmentioning
confidence: 65%
“…The full-length coding regions of hFXRa (NR1H4) were amplified by polymerase chain reaction (PCR) and cloned into KpnI-BamHI sites of pcDNA3.1(1) vector (Invitrogen, San Diego, CA) or into PstI-KpnI sites of pEnhanced GFP (green fluorescent protein)-N2 vector (Clontech, Mountain View, CA), respectively, to produce expression construct (pcDNA-hFXR) and GFP fusion FXRa (hFXR-GFP). The full-length cDNAs of retinoid X receptor (RXR) a and Set7/9 and SHP promoter were generated as described previously (Balasubramaniyan et al, 2012). The luciferase reporter plasmid of human bile salt export pump (hBSEP) was created by inserting its 59 untranslated region upstream (from bases 21250 to 165) at NheI-XhoI sites of the pGL4.17 [luc2/Neo] vector (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%